Pembelajaran Matematika SMP di Kota Surakarta pada Kondisi Khusus - Budiyono; Imam Sujadi; Ira Kurniawati; Arum Nur Wulandari; Riki Andriatna; Hanifa Puteri (Universitas Sarjanawiyata Tamansiswa, 2021)
The Covid-19 virus pandemic is declared a national disaster, so areas affected by the pandemic are declared to experience special conditions. This special condition causes a very rapid change in learning from face-to-face learning to learning from home (BDR). For this reason, this paper will describe a number of BDR activities for mathematics from the point of view of teachers and junior high school students in Surakarta City. The method used in this research is descriptive quantitative research. Data was collected by means of an online survey through a questionnaire in the form of a google form, accompanied by interviews for selected respondents. The survey results show three things. First, the way teachers are more varied in teaching. Second, the decrease in student interaction. Third, the number of students who understand the lesson is less than the number of students who do not understand the lesson. The results of the three studies indicate the need for mitigation efforts to prevent further declines in student learning outcomes, by providing recommendations for the implementation of activity-based learning that can be carried out when the area is in special conditions.